Modeling the interplay between emotion regulation, self-efficacy, and L2 grit in higher education - Zheng, Shengtao; Heydarnejad, Tahereh; Aberash, Amhara (Frontiers in Psychology, 2022)
Teaching in higher education is critical and fraught with potential vicissitudes, which necessitates the presence of efficient professors armed with positive attributes to perform effectively. Although it is generally accepted that emotion regulation (ER) has numerous benefits for language teachers, in particular university professors, little is known about how it interacts with two other important constructs, i.e., self-efficacy and L2 grit. Furthermore, the effect of ER on L2 teacher grit has not been sufficiently investigated. To fill this gap, the current study was to test a structural model of English as a Foreign Language (EFL) university professors’ ER, self-efficacy, and L2 grit. The participants were 356 Iranian EFL university professors who completed the Language Teacher Emotion Regulation Inventory (LTERI), the Teacher Sense of Efficacy Scale (TSES), and the L2-Teacher Grit Scale (L2TGS). The results of Structural Equation Modelling (SEM) revealed that ER and self-efficacy were strong predictors of L2 grit. Moreover, the significant role of self-efficacy on ER was discovered. The implications of this study may foster effective teaching in higher education, particularly during the COVID-19 pandemic and its impacts on education.